Studies on the Balkan Lepidoptera I - Stoyan Beshkov; Ana Nahirnić-Beshkova (Historia naturalis bulgarica, 2025)
New and interesting records of Balkan Lepidoptera are detailed. One genus and three species are new for the Balkan fauna, one of them, Chondrosoma fiduciaria Anker, 1854, is a species from Annex II of the EEC 92/43 Habitat Directive. Two other species and one subspecies are proven to be a part of the Balkan fauna. The majority of the species are from the informal group “Macrolepidoptera”, but we include as well as some representatives of the informal group “Microlepidoptera”. Seven genera and 33 species and one subspecies are new for Albania, and 20 species are reported for the second time. For Montenegro, three genera and 12 species are new. Three species are new for the Republic of North Macedonia, and the second locality is reported for three other species. The genus Sympistis and nine species are new and five species are reported for the second time for Serbia. One genus and three species are new to Bulgaria and five are reported for the second time. One genus and two species are new for Bosnia and Herzegovina. One genus and three species are new for Greece. Altogether, data for 442 species of Lepidoptera from more than 120 localities are presented here, and selected habitats, specimens, and their genitalia are illustrated in 359 figures.